Pinosylvin: A Multifunctional Stilbenoid with Antimicrobial, Antioxidant, and Anti-Inflammatory Potential - Argyrios Periferakis; Aristodemos-Theodoros Periferakis; Lamprini Troumpata; Konstantinos Periferakis; Spyrangelos Georgatos-Garcia; Georgia Touriki; Christiana Diana Maria Dragosloveanu; Ana Caruntu; Ilinca Savulescu-Fiedler; Serban Dragosloveanu; Andreea-Elena Scheau; Ioana Anca Badarau; et al. (Current Issues in Molecular Biology)
Stilbenoids are a category of plant compounds exhibiting notable health-related benefits. After resveratrol, perhaps the most well-known stilbenoid is pinosylvin, a major phytochemical constituent of most plants characterised by the pine spines among others. Pinosylvin and its derivatives have been found to exert potent antibacterial and antifungal effects, while their antiparasitic and antiviral properties are still a subject of ongoing research. The antioxidant properties of pinosylvin are mostly based on its scavenging of free radicals, inhibition of iNOS and protein kinase C, and promotion of HO-1 expression. Its anti-inflammatory properties are based on a variety of mechanisms, such as COX-2 inhibition, NF-κB and TRPA1 activation inhibition, and reduction in IL-6 levels. Its anticancer properties are partly associated with its antioxidant and anti-inflammatory potential, although a number of other mechanisms are described, such as apoptosis induction and matrix metalloproteinase inhibition. A couple of experiments have also suggested a neuroprotective potential. A multitude of ethnomedical and ethnobotanical effects of pinosylvin-containing plants are reported, like antimicrobial, antioxidant, anti-inflammatory, hepatoprotective, and prokinetic actions; many of these are corroborated by recent research. The advent of novel methods of artificial pinosylvin synthesis may facilitate its mass production and adoption as a medical compound. Finally, pinosylvin may be a tool in promoting environmentally friendly pesticide and insecticide policies and be used in land remediation schemes.